The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17712/nsj.2015.4.20150375
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of low-molecular-weight heparin and unfractionated heparin in the treatment of cerebral venous sinus thrombosis

Abstract: Objective:To compare the efficacy and safety of low-molecular-weight heparin (LMWH) and unfractionated heparin (UFH) in the treatment of patients with cerebral venous sinus thrombosis (CVST), and to provide an appropriate treatment option in these patients.Method:This is a randomized double blind clinical trial conducted between December 2013 and December 2014. The subjects were selected among patients referred to Neurology Department, Imam Reza Hospital; affiliated to Kermanshah University of Medical Sciences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…74 abstracts were screened, with 5 papers were read in full text. Three papers were suitable for analysis published between 2010 and 2015 [7], [8], [9]; 1 prospective cohort study and two randomized controlled trials (see Fig. 1 for the search strategy protocol) .…”
Section: Resultsmentioning
confidence: 99%
“…74 abstracts were screened, with 5 papers were read in full text. Three papers were suitable for analysis published between 2010 and 2015 [7], [8], [9]; 1 prospective cohort study and two randomized controlled trials (see Fig. 1 for the search strategy protocol) .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, two randomized controlled trials compared LMWH and UFH. The first showed a significantly lower mortality rate in the LMWH group (0% vs. 18.8%) , whereas the second showed no differences between the two groups in mortality (3.8% vs. 5.6%) and in new symptomatic intracranial hemorrhage (none in both groups) . UFH, with its shorter half‐life and easier reversibility, can be preferred in unstable patients or in those requiring invasive procedures.…”
Section: Treatment Of the Acute Phasementioning
confidence: 92%
“…33 After 2000, two additional small trials suggested that low-molecular-weight heparin (LMWH) was superior to unfractionated heparin (UFH). 34,35 Unfortunately, this evidence cannot be applied as such to the subgroup of dural STP. One of the two original trials excluded dural STP 31 ; the two more recent trials included it, but did not provide specific results for this patient subgroup.…”
Section: Anticoagulationmentioning
confidence: 99%
“…One of the two original trials excluded dural STP 31 ; the two more recent trials included it, but did not provide specific results for this patient subgroup. 34,35 Only two observational studies have specifically addressed anticoagulation in dural STP. A single-center analysis of 19 cases seen over 44 years suggested that heparin may reduce mortality in selected cases of septic cavernous sinus thrombosis.…”
Section: Anticoagulationmentioning
confidence: 99%